Translation as a learning tool in English for specific purposes - Kavaliauskienė, Galina; Kaminskienė, Ligija (Kalbotyra, 2007)
The state-of-the-art teaching of languages is based on the communicative method which emphasizes teaching English through English (Willis 1981). However, the idea of abandoning the native tongue is too stressful to many learners, who need a sense of security in the experience of learning a foreign language.In the past, the prevalence of grammar-translation method led to an extraordinary phenomenon: students were unable to speak fluently after having studied the language for a long time. For this reason, translation has been defined as “uncommunicative, boring, pointless, difficult, and irrelevant” (Duff, 1994).Recently there has been a revival of interest to translation due to the shift of its emphasis – to using a mother tongue as a resource for the promotion of language learning. Translation method develops three qualities essential to any language learning: accuracy, clarity, and flexibility (Duff 1994). Therefore, translation can serve as a tool for improving language skills.The goals of the paper are, firstly, to examine students’ perceptions of mother tongue application and mental translation in learning English for Specific Purposes (ESP), and secondly, to describe the activities which raise learners’ awareness of language use. Comparison between the L1 and L2 through translation can help learners to activate language usage and serve as a tool to polish up learners’ English.